The Use Of Cross – Functional Modules In Increasing The Environmental Thinking Of Students (Journal of Pedagogical Inventions and Practices, 2024)
This article presents information about the possibilities of using cross-functional modules, existing problems and their solutions in increasing the environmental thinking of students. Various techniques and tools used by developed countries in the field of environmental education are also covered. The student reflected on the need for sustainable environmental education in the development of environmental thinking of young people..